IMPLEMENTASI UPAYA PEMANFAATAN Pinus merkusii DI DESA NGRAYUDAN, JOGOROGO, NGAWI - Agnafia, Desi Nuzul; Anfa, Qurrotul; Widyawati, Ratna Tri; Khoirunnisa, Fatimah; Rahmawati, Rizka Novia (Biospecies, 2026)
Pine forests (potential. However, their utilization by communities around forest areas is still limited, Pinus merkusii) are a forest resource with great economic, ecological, and social especially in terms of getah tapping and the use of the area as a tourist attraction. This study aims to analyze community efforts in utilizing P. merkusii in the Selo Ondo tourist area, Ngrayudan Village, Jogorogo District, Ngawi Regency, and to identify other potential uses that have not been optimized. This study employs a qualitative descriptive research method through direct observation and interviews with communities surrounding the tourist area. Data analysis is conducted using data reduction, data presentation, and data verification techniques. The results show that the utilization of pine trees by the community is still not optimal and has not led to the diversification of value-added products. Utilization is still focused on pine sap and environmental services in the form of nature tourism. Meanwhile, other parts of the pine tree, such as needles, flowers, and organic waste, have great potential to be developed as bioenergy products, handicrafts, and educational ecotourism support. Lack of knowledge, skills, and guidance are the main factors hindering the optimization of pine utilization.